Inflation expectations and their role in Eurosystem forecasting (European Central Bank (ECB), 2021)
This paper summarises the findings of the Eurosystem's Expert Group on Inflation Expectations (EGIE), which was one of the 13 work streams conducting analysis that fed into the ECB's monetary policy strategy review. The EGIE was tasked with (i) reviewing the nature and behaviour of inflation expectations, with a focus on the degree of anchoring, and (ii) exploring the role that measures of expectations can play in forecasting inflation. While it is households' and firms' inflation expectations that ultimately matter in the expectations channel, data limitations have meant that in practice the focus of analysis has been on surveys of professional forecasters and on market-based indicators.Regarding the anchoring of inflation expectations, this paper considers a number of metrics: the level of inflation expectations, the responsiveness of longer-term inflation expectations to shorter-term developments, and the degree of uncertainty. Different metrics can provide conflicting signals about the scale and timing of potential unanchoring, which underscores the importance of considering all of them. Overall, however, these metrics suggest that in the period since the global financial and European debt crises, longer-term inflation expectations in the euro area have become less well anchored. Regarding the role measures of inflation expectations can play in forecasting inflation, this paper finds that they are indicative for future inflationary developments. When it comes to their predictive power, both market-based and survey-based measures are found to be more accurate than statistical benchmarks, but do not systematically outperform each other. Beyond their role as standalone forecasts, inflation expectations bring forecast gains when included in forecasting models and can also inform scenario and risk analysis in projection exercises performed using structural models. In terms of the implications for the ECB's economic and monetary analysis going forward, the work of the EGIE essentially highlights the need for (i) more data on households' and firms' inflation expectations, (ii) a comprehensive framework for assessing (un)anchoring and (iii) further considerations regarding the use of observed expectation measures in forecasting models.
Keywords: D84; E31; E37; E52; 330; Inflation expectations; anchoring; forecasting; macroeconomics; monetary policy